Analisis Penggunaan Kakujoshi no (の) Pada Website Portal Berita NHK Japan Menggunakan Teknik Web Scraping - Mario Raditya Nugroho; Fadly Kurniawan; Muhammad Rahmat Maryadi; Rayhan ananda hafiz Pradipta; Humannisa Rubina Lestari (IZUMI, 2025)
This study investigates the distribution and syntactic-semantic functions of the Japanese case particle no (の) in news articles published on NHK News Web Easy during March 2025. The aim is to provide a descriptive analysis of how the particle no operates within simplified Japanese news texts. Data were collected using web scraping techniques through the ParseHub platform, allowing automated and structured extraction of 80 articles. 508 instances of no were identified and manually analyzed to classify their linguistic functions. The findings show that the most dominant function is a nominal connector, accounting for 422 occurrences, followed by functions such as indicating origin, possession, spatial relationships, and conversational emphasis. The pattern Nominal₁ + no + Nominal₂ was found to be the most common syntactic structure across the dataset. This reflects the critical role of no in forming meaningful and information-dense phrases even within simplified Japanese texts. The combination of automatic data retrieval and manual linguistic analysis in this research highlights the effectiveness of integrating technology and qualitative approaches in language studies. The results contribute to understanding authentic Japanese grammatical usage and provide pedagogical insights for teaching Japanese as a foreign language. Future research is encouraged to expand the scope with longitudinal data and semi-automated analysis tools for broader linguistic coverage. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor